Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening (Studi pada Perusahaan Manufaktur Yang Listing Di Bursa Efek Indonesia Periode 2009-2012) - Redi Khoirianto (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2016)
The main objective of the study is to examine the impact ofprofitability, dividend policy, and capital structure on firms value inIndonesia Stock Exchange (IDX). Population in this study are publiccompany listed in Indonesia Stock Exchange during 2009-2012. The datawere then analyzed by the multiple regression analysis, using the SPSSProgram version 16.0. The results of this study show that (1) profitabilityhave positive and significant influence on capital structure, (2) profitabilityhave negative and significant influence on capital structure, (3) profitabilityhave positive and significant influence on firm value, (4) dividend policyhave not significant influence on firm value, (5) capital structure havenegative and significant influence on firm value, (6) profitability havesignificant influence on firm value weather capital structure, (7) devidentpolicy have significant influence on firm value weather capital structure, (8)by simultan profitability, dividend policy, and capital structure havesignificant influence on firm value